2014
DOI: 10.1051/0004-6361/201322230
|View full text |Cite
|
Sign up to set email alerts
|

New near-infrared observations and lens-model constraints for UM673

Abstract: Aims. We performed a detailed photometric analysis of the lensed system UM673 (Q0142-100) and an analysis of the tentative lens models. Methods. High-resolution adaptive optics images of UM673 taken with the Subaru telescope in the H band were examined. We also analysed the J, H and K-band observational data of UM673 obtained with the 1.3 m telescope at the CTIO observatory.Results. We present photometry of quasar components A and B of UM673, the lens, and the nearby bright galaxy using H-band observational da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Lagattuta, Auger, & Fassnacht (2010) analysed the quad B0128+437 by iteratively fitting a PSF modelled as three Gaussian components, together with the lensing galaxy modelled with a Sersic profile. Koptelova et al (2014) modelled the PSF for a lensed double by using a hybrid composed of the observed brightness distribution of the bright image at the centre, and analytical wings.…”
Section: Techniques Used In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Lagattuta, Auger, & Fassnacht (2010) analysed the quad B0128+437 by iteratively fitting a PSF modelled as three Gaussian components, together with the lensing galaxy modelled with a Sersic profile. Koptelova et al (2014) modelled the PSF for a lensed double by using a hybrid composed of the observed brightness distribution of the bright image at the centre, and analytical wings.…”
Section: Techniques Used In the Literaturementioning
confidence: 99%
“…There is enough information (e.g., Marshall et al 2007) in the multiple images of a lensed system to reconstruct the PSF. In this paper, we combined the approach of Lagattuta, Auger, & Fassnacht (2010) and Koptelova et al (2014) into a new technique, by adopting an analytical PSF model and simultaneously optimising for the global PSF parameters as well as the individual objects comprising the system: multiple point sources, and the lensing galaxy modelled as a Sersic profile convolved with the PSF. Where possible, we take an additional step where we refine this fit by using a hybrid PSF (Section 3.4).…”
Section: Modelling With An Analytical Psfmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive optics observations may also improve the information about the structure of the lens system, and deep NIR images are valuable diagnostic tools. In particular, a new deep image in the H band could reveal details about the brightness profile of G and the galaxy field around SDSS J1339+1310 (e.g., Koptelova et al 2014, and references therein). These H-band data may be used to look for galaxies in the vicinity of G, adequately study the galaxy clustering, and estimate its associated convergence/shear.…”
Section: Discussionmentioning
confidence: 99%
“…A discussion on the origin of the external shear requires accurate data of the galaxy field around SDSS J1339+1310 (see recent papers by Anguita et al 2009;MacLeod et al 2009;Goicoechea & Shalyapin 2010;Wong et al 2011;Koptelova et al 2014). There are no SDSS galaxies within a 20 radius circle around the lens system (≤130 kpc at z ∼ 0.6).…”
Section: Lens Modelsmentioning
confidence: 99%